Correlation Between Occurrence and Deterioration of Respiratory Diseases and Air Pollution Within the Legally Permissible Limits - Kristina Trnjar; Sanja Pintarić; Marko Mornar Jelavić; Višnja Nesek; Jelena Ostojić; Sanja Pleština; Aljoša Šikić; Hrvoje Pintarić (Acta Clinica Croatica, 2017)
The aim of the study was to investigate the unknown effect of air pollutants on the occurrence or deterioration of respiratory diseases in the area with a humid continental climate. This retrospective study included 5868 patients with respiratory symptomatology (upper respiratory tract infection (URTI), pneumonia, acute bronchitis, chronic obstructive pulmonary disease (COPD), and asthma) admitted to emergency department (ED). The number of patients, values of meteorological parameters (mean daily values of air temperature pressure and relative humidity) and concentrations of air pollution particles (≤10 μm (PM10), ozone (O3) and nitrogen dioxide (NO2)) were collected during a two-year ( July 2008 – June 2010) period. There were 1839 (31.3%), 1712 (29.2%), 1313 (22.4%), 614 (10.5%) and 390 (6.6%) patients with pneumonia, COPD, URTI, acute bronchitis and asthma, respectively. The mean daily concentrations of NO2 (25.9 (1.7-89.7) μg/m3), O3 (47.1 (4.7-135.4) μg/m3) and PM10 particles (25.7 (4.6-146.6) μg/m3) were below the legally defined thresholds. Among other results, the occurrence of respiratory diseases showed positive Spearman’s correlation with the values of air humidity (days 0-3, r=0.15 to 0.19), PM10(days 0-3, r=0.10 to 0.13) and NO2 concentrations (day 0, r=0.11), and negative correlation with the values of air temperature (days 0-3, r=-0.36 to -0.34), pressure (day 0, r=-0.10) and O3 concentrations (days 0-3, r=-0.21 to -0.22) (p<0.05 all). In conclusion, the occurrence of respiratory diseases showed correlation with weather conditions and air pollutants despite the legally permitted values in the region with a humid continental climate.